Shear interfacial viscoelasticity of native and hydrophobically modified xanthan at oil/water interface. (December 2016) - Roy, Audrey N.; Benyahia, Lazhar; Grisel, Michel; Renou, Frederic
Abstract: In this study, we investigate the shear viscoelasticity of xanthan and hydrophobically modified xanthans at silicone oil/water interface. Xanthan is well known to adopt two distinct conformations in water solution, a rigid conformation at low temperature and a flexible one at high temperature. Hence, we first studied the un-modified xanthan as a function of temperature and showed that its interfacial viscoelasticity depends on the xanthan conformation as in bulk but evolves the opposite way after heating: i.e., the bulk viscoelasticity is weakened after thermal treatment while interfacial viscoelasticity is reinforced. Ergo, we proved that for xanthan, bulk and interfacial viscoelastic properties act independently. Then, we investigated the effect of hydrophobic modification of xanthan on its interfacial properties. We demonstrated that, before any thermal treatment, the more grafted the polymer, the higher the interfacial elasticity confirming the potential stabilizing properties of such modified polysaccharides. The interfacial properties of modified xanthans are also improved after thermal treatment but the improvement is much less pronounced for grafting densities above 8% which is explained by different chains organization at the interface. Graphical abstract: Highlights: Bulk and interfacial viscoelastic properties act independently. Modified xanthans exhibit strong improvement of the interfacial viscoelasticity. A net improvement after thermal treatment is observed. The improvement is related to the xanthane helix-coil transition at the interface.